Strategi Pengembangan Literasi Keuangan Syariah Dalam Meningkatkan Jumlah Nasabah BPRS Lantabur Tebuireng Cabang Surabaya - Ayatullah , Muhammad Nur; Zainuddin Akbar Bahrun; Muhammad Hamdan Ali Masduqie; Shinta Hardiyanti, Istiqom; Afri Suhairi Panjaitan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of developing Islamic financial literacy for BPRS Lantabur Tebuireng Surabaya Branch begins with the adjustment of the Financial Services Authority regulations related to routine reporting of Islamic financial literacy in each bank, including BPRS. Furthermore, in order to provide knowledge or self-introduction to the people of the City of Surabaya who are still used to Conventional Banks. On the other hand, the target for 2022 is to get customers, namely using the Bank's Business Plan (RBB), starting from the target of financing, funding, and profit. Therefore, BPRS Lantabur Tebuireng Surabaya Branch is looking for customers whose needs are adjusted to meet the criteria categorized by the bank. In addition to providing financial literacy to prospective new customers, BPRS Lantabur Tebuireng Surabaya Branch also provides Islamic financial literacy to existing customers directly. Thisresearch uses a qualitative method with a case study approach that examines the Strategy for Developing Islamic Financial Literacy in Attracting Customers of BPRS Lantabur Tebuireng Surabaya Branch. The results of this study can be explained that in order to carry out Islamic financial literacy in attracting customers, evaluations continue to be carried out, one example is the removal of the brochure sharing method because it is considered ineffective. The new method is to create events, collaborate with institutions, hold certain moments such as milad Lantabur and Milad BPRS in Indonesia country as well as the reference.